Evaluation of the effectiveness of local Melatonin applied at different doses on healing of bone defect in rat tibias - Tanrisever, Murat; Bereket-Altintas, Muge; Can, Umit Koray; Istek, Ozmen; Ozcan, Erhan Cahit; Ozercan, Ibrahim Hanifi; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
This study aimed to investigate the effect of local melatonin application on bone healing in critical size defects created in tibias. 30 Spraque Dawley rats selected for the experimental setup were divided into three groups, each with 10 rats. In the control-defect group (n=10), only defects were created in the tibia bones the rats, while 1.2 mg and 3 mg melatonin were applied locally to the defect-melatonin dose 1 (n=10) and defect melatonin dose 2 (n=10) groups, respectively. At the end of the experiment the subjects all the groups were euthanized after an 8-week healing period and defect healing was calculated with histological bone healing percentage. The Shapiro-Wilk test and the Kolmogorov-Smirnov test were used to evaluate the conformity of the data to a normal distribution. One-way ANOVA was used to determine whether there was a difference between the groups due to the normal distribution of the data, and Tukey's honestly significant difference (HSD) test was used in pairwise comparisons to determine from which group the difference originated. The healing rate in the defect melatonin dose 2 group was calculated as 53.2 +/- 7.38% and the healing rate in the control group was calculated as 44 +/- 6.38%, which was a significant increase (P=0.008); however, when the difference between the defect melatonin dose 1 group (53 +/- 7.1%) and the defect melatonin dose 2 group (53. 2 +/- 7.38%) was evaluated statistically, no significant difference was found.The bone healing percentage in the groups where local melatonin was applied was found to be statistically significantly higher compared to the control group (P<0.05). No statistically significant difference was found between the groups where local melatonin was applied in terms bone healing percentage (P>0.05). Within the limits of this study, can be said that local melatonin application applied at two different doses had a positive effect on bone healing, however, no difference was observed between the applied local melatonin doses in terms of bone healing.
Evaluación de la efectividad de la melatonina local aplicada a diferentes dosis en la curación de defectos óseos en tibias de rata
Keywords: Bone; defect; local melatonin; rat tibia